Immunotherapy for pancreatic ductal adenocarcinoma. Issue 3 (17th February 2021) - Carpenter, Eileen; Nelson, Sarah; Bednar, Filip; Cho, Clifford; Nathan, Hari; Sahai, Vaibhav; di Magliano, Marina Pasca; Frankel, Timothy L.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains a lethal cancer with an urgent need for better medical therapies. Efforts have been made to investigate the efficacy of immunotherapy, particularly given the hallmarks of immune suppression and exhaustion in PDAC tumors. Here, we review the molecular components responsible for the immune‐privileged state in PDAC and provide an overview of the immunotherapeutic strategies for PDAC including vaccine therapy, checkpoint blockade, myeloid‐targeted therapy, and immune agonist therapy.